Advance care planning and end‐of‐life care in a network of rural Western Australian hospitals. (1st July 2015) - Auret, Kirsten; Sinclair, Craig; Averill, Barbara; Evans, Sharon
Abstract Objective To provide a current perspective on end‐of‐life (EOL) care in regional Western Australia, with a particular focus on the final admission prior to death and the presence of documented advance care planning (ACP). Design Retrospective medical notes audit. Setting One regional hospital (including colocated hospice) and four small rural hospitals in the Great Southern region of Western Australia. Participants Ninety recently deceased patients, who died in hospitals in the region. Fifty consecutive patients from the regional hospital and 10 consecutive patients from each of the four rural hospitals were included in the audit. Interventions A retrospective medical notes audit was undertaken. Main outcome measures A 94‐item audit tool assessed patient demographics, primary diagnosis, family support, status on admission and presence of documented ACP. Detailed items described the clinical care delivered during the final admission, including communication with family, referral to palliative care, transfers, medical investigations, medical treatments and use of EOL care pathways. Results Fifty‐two per cent were women; median age was 82 years old. Forty per cent died of malignancy. Median length of stay was 7 days. Thirty‐nine per cent had formal or informal ACP documented. Rural hospitals performed comparably with the regional hospital on all measures. Conclusions This study provides benchmarking information that can assist other rural hospitals and suggests ongoing work on optimal methods of measuring quality in EOL care.